Scolopendra subspinipes mutilans L. Koch Ameliorates Rheumatic Heart Disease by Affecting Relative Percentages of CD4+CD25+FoxP3 Treg and CD4+IL17 T Cells. (14th July 2019) - Jiang, Tiechao; Zhao, Qini; Sun, Hongyan; Zhang, Lirong; Song, Shanshan; Chi, Hongli; Zhou, Hui
Abstract : Scolopendra subspinipes mutilans L. Koch. (SSLK) helps reduce the risk of coronary heart disease (CHD) but its effects on rheumatic heart disease (RHD) patients remain unclear . 80 RHD patients were recruited and randomly assigned into SG (to receive SSLK treatment) and CG (to receive placebo) groups, and the intervention lasted for 3 months. The following cardiac indexes were measured, including mean arterial pressure (MAP), heart rate (HR), central venous pressure (CVP), blood lactate, fatigue, shortness of breath, palpitation, and chest pain. ELISA kits were used to analyze creatine kinase isoenzyme (CK-MB), serum troponin T (cTnT), CRP, IL-1 β, IL-6, and TNF- α, malondialdehyde (MDA), and superoxide dismutase (SOD). Relative percentages of CD4 + CD25 + FoxP3 regulatory (Treg) and CD4 + IL-17 T cells were measured using flow cytometry. After 3-month therapy, SSLK intervention improved MAP, HR, CVP, fatigue, palpitation, and shortness breath of CHD patients, reduced the levels of blood lactate, CK-MB, cTnT, CRP, IL-1 β, IL-6, TNF- α, MDA, and increased SOD level ( p < 0.05). Meanwhile, SSLK treatment increased the percentages of CD4 + CD25 + FoxP3 Treg cells and reduced relative percentages of CD4 + IL-17 T cells in a dose-dependent way ( p < 0.05). Relative percentage of CD4 + CD25 + FoxP3 Treg cells had negative relationship while CD4 + IL17 T cells had positive relationship with CK-MB, cTnT, CRP, and TNF-a ( p < 0.01). SSLK ameliorated RHD by affecting the balance of CD4 + CD25 + FoxP3 Treg and CD4 + IL17 T cells.